INTERCULTURAL COMMUNICATIVE COMPETENCE (ICC) IN TEACHING SPEAKING MATERIAL USED IN ENGLISH DEPARTMENT OF UNIVERSITAS NEGERI SEMARANG - Saraswati, Girindra Putri Dewi (Language Circle: Journal of Language and Literature, 2017)
This study aims at finding out a concrete picture of intercultural-bound English speaking material used in English department of UniversitasNegeri Semarang. Specifically, this study deeply examines the intercultural component attached in English teaching material used in speaking classroom by employing Intercultural Communicative Competence theory. This study uses qualitative method, and case study design. The data was collected by using observation, interview, as well as documentation study techniques; and was validated by using triangulation method which encompasses data source triangulation, researcher triangulation, theory triangulation, as well as methodology triangulation. Results show that the teaching material in form of textbook used by lecturers in English Department of UniversitasNegeri Semarang has implicitly and explicitly embedded the aspect of intercultural communication in a form of politeness. It was shown from the explanation, practices, as well as degree of formality provided in the textbook that the speaking material attempts to emphasize the teaching of culture in terms of politeness acceptable in the target language. Future research needs to be conducted focusing on kinds of politeness which have to be mastered by the students.